Assessment of quality of life in adolescents with obesity associated with polymorphisms of the lactase gene - Abaturov A.E.; Nikulina A.A. (Medičnì Perspektivi)
The growing obesity incidence in adolescents on the background of insufficiently studied genetic markers of formation of impairments of carbohydrate metabolism associated with the lactase gene polymorphism (SNP LCT), necessitates studying life quality particularly in this age group. Associations of 13910 C>T polymorphism of lactase gene with the quality of life in 60 adolescents aged 14-18 with obesity using the MOS-SF-36 technique (MOS 36-item Short-Form Health Survey) were studied. It was established the presence of associations of the genotype C/C 13910 of the LCT gene (p<0,05) with decrease of role functioning due to physical condition of young men and decrease of the overall health of girls. Prevention of obesity should start from birth of the newborn to gether with the rational organization of alimentary behavior in the family as a whole, depending on the phenotype and formation of a certain psychotype of adolescent’s personality, defined by the lactase gene polymorphism.